2011
DOI: 10.3390/medicina47100077
|View full text |Cite
|
Sign up to set email alerts
|

Are Paclitaxel-Eluting Stents Better in Unprotected Left Main Coronary Artery Disease? Three-Year Clinical and Intravascular Imaging Results From a Randomized Study

Abstract: Background and Objective. Recent publications have demonstrated superior outcomes in unprotected left main patients after paclitaxel-eluting stent (PES) implantation. Long-term data in these patients are limited. The aim of this study was to evaluate if intravascular ultrasound (IVUS)-guided PES implantation is superior to bare metal stent (BMS) implantation in unprotected left main disease after lesion pretreatment with cutting balloon during long-term follow-up. Material and Methods. Unprotected left main pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Among patients randomized to a planned two-stent strategy in the EBC Main, plaque pretreatment with cutting balloon, rotablation, or lithotripsy was undertaken in 22% of main vessels and 15% of side branches. The lower mortality rate in the present study may be in part related to our learning curve gained from the first randomized trial (2004–2006) comparing DES and bare-metal stent for left main intervention, which showed a 2% death rate at 6 months and 7% at 3 years [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients randomized to a planned two-stent strategy in the EBC Main, plaque pretreatment with cutting balloon, rotablation, or lithotripsy was undertaken in 22% of main vessels and 15% of side branches. The lower mortality rate in the present study may be in part related to our learning curve gained from the first randomized trial (2004–2006) comparing DES and bare-metal stent for left main intervention, which showed a 2% death rate at 6 months and 7% at 3 years [ 8 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 The cytotoxic, anti-proliferative effect of DES on the vessel wall has been widely explored. 2,4 Preclinical studies with DCB have shown that 3 mg mm À2 paclitaxel is the effective dose to achieve an efficient, long-term, antiproliferative effect on the vessel wall. 2,5 Drug delivery during angioplasty depends on drug dose, transfer system, dilation time, release pattern and appropriate balloon coating.…”
Section: Introductionmentioning
confidence: 99%